Sola Scriptura! the Protestant position on the Bible - Sproul, Robert Charles, Dr 1939-; Armstrong, John Dr; Macarthur, John Dr; Beeke, Joel, Dr; Lanning, Ray, Rev.; Kistler, Don, Rev.; Godfrey, W. Robert, Dr; White, James, Rev.; Ferguson, Sinclair B, Dr, 1948- (Morgan, PA Soli Deo Gloria, 1995)
Includes bibliographcail references.
Keywords: Bible -- authority -- religious aspects -- protestant